Trusting the bankers: A new look at the credit channel of monetary policy - Matteo Ciccarelli; Angela Maddaloni; José-Luis Peydró (Review of Economic Dynamics, 2015)
Credit supply and demand changes are mostly unobserved, thus identifying completely the transmission of monetary policy through the credit channel is unfeasible. Bank lending surveys by central banks, however, contain reliable quarterly information on changes in loan conditions due to bank, firm and household balance sheet strength and on changes in loan demand. Using the U.S. and the unique Euro area surveys, we find that the credit channel amplifies a monetary policy shock on GDP and prices, through the balance-sheets of households, firms and banks. For corporate loans, amplification is highest through the bank lending and the borrower's balance sheet channel; for households, demand is the strongest channel.
Keywords: E32; E44; G01; G21; 330; credit channel; firm and household balance-sheet channels; bank lending channel; credit crunch; credit supply; monetary policy